Population Variables of stabilities countryside in Shatt al - Arab District in Basrah Governorate - Republic of Iraq - Al-Eidani, Abbas Abdul-Hasan Kazem; Al-Tamimi, Lama Ghazi Awfi (Arab Journal for Sciences and Research Publishing, 2017)
These Studies have Contributed in the population growth analysis in stabilities countryside the Shatt Al- Arab in Basra Asti Faced the study area increased in population resulting From the sale of agricultural land and turn into new housing The population , They were in country side of distinct for the year 1987 is (16871) people(person) because of Iran-Iraq War and then the conditions of the year 2009 rose to (88593) people, and will reach the population in 2014 to (114073) people , according to demographic equation stabilities population as immigration plugged to the study area after the year 2003 role in the increase in the number of its population and this threatens agricultural production and decreasing acreage.